Inhaled sevoflurane may promote progression of amnestic mild cognitive impairment: a prospective, randomized parallel-group study - Liu, Yongzhe; Pan, Ningling; Ma, Yaqun; Zhang, Shengshuo; Guo, Wenzhi; Li, Haihong; Zhou, Jingli; Liu, Gang; Gao, Minglong (The American journal of the medical sciences, 2013)
Amnestic mild cognitive impairment (aMCI) is thought to be a transitional stage between normal aging and the development of Alzheimer's disease (AD). Recent studies have suggested that the inhalational anesthetic isoflurane can induce caspase activation and apoptosis, increase aggregates of β-amyloid (Aβ) levels, and enhance Aβ aggregation. The aim of this study was to investigate whether previous exposure to different anesthetics induced progression of aMCI. A prospective, randomized parallel-group study was completed with 180 patients with aMCI who were randomly assigned to a sevoflurane, propofol or lidocaine epidural anesthesia group (n = 60 per group) during an L3 to L4 or an L4 to L5 spinal surgery. Sixty additional outpatients with aMCI served as a control group. Before surgery, all subjects underwent a neuropsychological assessment. Cerebrospinal fluid (CSF) was obtained by lumbar puncture, and neuropsychological assessments were completed in the clinic. CSF Aβ42, total tau and phosphorylated tau181 were quantitatively assayed. The neuropsychological assessments were repeated after 2 years. Two years after anesthesia, the number of AD cases that emerged did not differ significantly between the groups. However, the number of cases of progressive MCI was greater in the sevoflurane group than in the control group. Age correlated linearly with aMCI progression, whereas sex did not. Both patients with AD and progressive MCI had decreased CSF Aβ42, increased total tau and increased phosphorylated tau levels compared with those with stable MCI and the controls. Inhaled sevoflurane accelerated the progression of aMCI to progressive MCI in this selected Chinese population.